PENGARUH PENYERAPAN RADIASI SURYA PADA MEDIA TIPE KOTAK DAN BERGELOMBANG BERBAHAN DASAR STAINLESS STEEL TERHADAP KEMAMPUAN DESTILASI AIR PAYAU DI PESISIR PANTAI SEBA - Dedy Nataniel Ully; Rokhyadi Rokhyadi; Duma Pabiban (Jurnal Ilmiah Flash, 2017)
The use of solar radiation absorber on box and corrugated media can improve the ability orperformance of the brackish water distillation process into freshwater. This process of brackishwater distillation is to separate the excessive salt elements contained in brackish water, by heatingby using solar energy so that evaporation takes place within the distillator and under certainconditions will experience condensation, so that the hot vapor turns phase into water because itcomes into contact with a cold glass surface. Thus, the water will be obtained clean and not saltyanymore. While salt water will be left in the container destilator because there are elements ofsalt in which have a larger density. This study was conducted using real experimental method (true experimental) on laboratory scale. The test is done at 8:00 until 16:00 with the volume of water inthe distillator as much as 35 liters. The results show that efficiency increases in parabolic over time butdecreases above at 14.00. This happens because the intensity of solar radiation will decrease along withthe sun’s incline to the west, so the heat received by the destilator decreases. The highest efficiencyoccurs at 12.00 ie on the absorbent type of box of 16.72% while the absorbent type of wave surgeshighest efficiency also occurs at 12:00 at 12.509%, this happens because at this time the sun radiatessuryanya maximum.